2019
DOI: 10.1093/pm/pnz290
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Directed Repetitive Transcranial Magnetic Stimulation in Acute Neuropathic Pain After Spinal Cord Injury

Abstract: Objectives Central neuropathic pain (CNP) often appears following spinal cord injury (SCI), but current treatments are not always successful. In this study, we evaluated the analgesic effects of repetitive transcranial magnetic stimulation (rTMS) applied over the hand area of the motor cortex in patients with acute CNP after SCI. Methods A total of 48 patients with complete or incomplete SCI and acute CNP participated in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…However, the analgesic effects of rTMS for acute and subacute pain have been less studied. Few studies have been performed on postsurgical pain ( 23 ), pain after spinal cord injury (SCI) ( 24 ), and experimental model pain. In addition, there are no data available on subacute CPSP ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the analgesic effects of rTMS for acute and subacute pain have been less studied. Few studies have been performed on postsurgical pain ( 23 ), pain after spinal cord injury (SCI) ( 24 ), and experimental model pain. In addition, there are no data available on subacute CPSP ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous randomized controlled trial (RCT), which was intended to investigate the analgesic effects of rTMS specifically on neuropathic pain in patients with SCI [ 18 ], revealed that 10 Hz rTMS produced transient analgesic effects from the third day to the first week. In the present study, using the same parameters as the previous trial, the pain intensity was lowest on the seventh day, and this analgesic effect lasted until the third week.…”
Section: Discussionmentioning
confidence: 99%
“…We used a neuronavigation system (visor2, ANT Neuro b.v., Enschede, Netherlands) to guide the magnetic stimulation, as described previously [ 18 ]. The system generated a three-dimensional reconstruction of the patient’s brain based on magnetic resonance imaging (MRI) data obtained before the first session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient was enrolled and her first navigated rTMS treatment was carried out at the Department of Neurology, Xijing Hospital on July 27, 2020, with a CCY-1 stimulator (Yiruide Medical Equipment Company, China) using a figure 8 coil, following the safety guidelines and protocols for rTMS [3]. Navigation was performed using a neuronavigational system (visor2, ANT Neuro, Enschede, Netherlands) to guide the magnetic stimulation as previously described [4]. Briefly, before the first rTMS session, T1-weighted magnetic resonance imaging of the patient was integrated into the navigation system and a three-dimensional reconstruction of the patients' brain was generated accordingly.…”
Section: Navigated Rtms Treatmentmentioning
confidence: 99%